"We've all got the virus inside us now": Disaggregating public health relations and responsibilities for health protection in pandemic London. (September 2022) - Kasstan, Ben; Mounier-Jack, Sandra; Gaskell, Katherine M.; Eggo, Rosalind M.; Marks, Michael; Chantler, Tracey
Abstract: The COVID-19 pandemic has disproportionately impacted ethnic minorities in the global north, evidenced by higher rates of transmission, morbidity, and mortality relative to population sizes. Orthodox Jewish neighbourhoods in London had extremely high SARS-CoV-2 seroprevalence rates, reflecting patterns in Israel and the US. The aim of this paper is to examine how responsibilities over health protection are conveyed, and to what extent responsibility is sought by, and shared between, state services, and 'community' stakeholders or representative groups, and families in public health emergencies. The study investigates how public health and statutory services stakeholders, Orthodox Jewish communal custodians and households sought to enact health protection in London during the first year of the pandemic (March 2020–March 2021). Twenty-eight semi-structured interviews were conducted across these cohorts. Findings demonstrate that institutional relations – both their formation and at times fragmentation – were directly shaped by issues surrounding COVID-19 control measures. Exchanges around protective interventions (whether control measures, contact tracing technologies, or vaccines) reveal diverse and diverging attributions of responsibility and authority. The paper develops a framework of public health relations to understand negotiations between statutory services and minority groups over responsiveness and accountability in health protection. Disaggregating public health relations can help social scientists to critique who and what characterises institutional relationships with minority groups, and what ideas of responsibility and responsiveness are projected by differently-positioned stakeholders in health protection. Highlights: COVID-19 produced diverse responses and relations around health protection in London. Pandemic preparedness can be enhanced by mapping possible partners in localities. Establishing public health partnerships requires adequate resources. Public health services cannot defer responsibility entirely to local partners. Households are key constituents of public health relations.